Chemoimmunotherapy in the First-Line Treatment of Chronic Lymphocytic Leukaemia: Dead Yet, or Alive and Kicking? - Smolej, Lukáš; Vodárek, Pavel; Écsiová, Dominika; Šimkovič, Martin (Cancers, 2021)
The paradigm of first-line treatment of chronic lymphocytic leukaemia (CLL) is currently undergoing a radical change. On the basis of several randomised phase III trials showing prolongation of progression-free survival, chemoimmunotherapy is being replaced by treatment based on novel, orally available targeted inhibitors such as Bruton tyrosine kinase inhibitors ibrutinib and acalabrutinib or bcl-2 inhibitor venetoclax. However, the use of these agents may be associated with other disadvantages. First, with the exception of one trial in younger/fit patients, no studies have so far demonstrated benefit regarding the ultimate endpoint of overall survival. Second, oral inhibitors are extremely expensive and thus currently unavailable due to the absence of reimbursement in some countries. Third, treatment with ibrutinib and acalabrutinib necessitates long-term administration until progression; this may be associated with accumulation of late side effects, problems with patient compliance, and selection of resistant clones. Therefore, the identification of a subset of patients who could benefit from chemoimmunotherapy would be ideal. Current data suggest that patients with the mutated variable region of the immunoglobulin heavy chain (IGHV) achieve fairly durable remissions, especially when treated with fludarabine, cyclophosphamide, and rituximab (FCR) regimen. This review discusses current options for treatment-naïve patients with CLL.
Keywords: chronic lymphocytic leukaemia; obinutuzumab; ibrutinib; direct inhibitors; venetoclax; prognosis; rituximab; chemoimmunotherapy; acalabrutinib